HUBUNGAN ANTARA PARAMETER FISIK DENGAN KANDUNGAN ESCHERICHIA COLI PADA KOLAM RENANG UMUM DI KOTA PADANG TAHUN 2025 - Loly Novita Winas; Cici Aprilliani; Fauzan Akbar; Widya Yunita Fitri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Public swimming pools have the potential to become a medium for disease transmission if the water quality does not meet health standards. This study was motivated by the high risk of Escherichia coli (E. coli) contamination in public swimming pools in Padang City. The objectives of this study were to assess the physical parameters of the pool water (temperature, turbidity, odor, and swimmer density), detect the presence of E. coli, and analyze the relationship between the two. This study was a quantitative cross-sectional study using total sampling. The study sample consisted of 10 public swimming pools in Padang City that met the inclusion criteria. Data were obtained through field observations and laboratory tests, then analyzed using Spearman's correlation test with a significance level of 95%. The results showed that temperature and swimmer density mostly met the requirements, while turbidity (80%) and odor (100%) did not meet the requirements. A total of 70% of swimming pools tested positive for E. coli. Statistical tests showed that only turbidity was significantly associated with the presence of E. coli (p 0.05). In conclusion, the physical quality of public swimming pool water in Padang City does not fully meet standards, especially in terms of turbidity and odor. It is recommended that managers strengthen filtration and disinfection systems, conduct routine laboratory tests, and control the number of swimmers to prevent public health risks. Keywords: Public Swimming Pools, Physical Parameters, Escherichia Coli, Water Quality